Гравийные фильтры с использованием эффекта двухфазного инверсного перехода агрегатного состояния вяжущего вещества - Кожевников, А.А.; Судаков, А.К.; Гриняк, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The analysis of technologies of equipment of drillholes gravelers is in-process conducted,
and also pre-conditions are considered for creation of untraditional technology of equipment of waterreceiving part of drillholes by gravelers, made with the use of effect of diphasic inversion transition of the aggregate state of astringent matter.